Interrelationship between Rainfall Index and Nifty Index: An Empirical Study - N, Dileep; Kotreshwar, G. (Gyan Management Journal, 2022)
The proposed study is an attempt to determine whether a relationship exists between rainfall index and NSE Nifty index. The study used the monthly mean rainfall data and monthly closing price of Nifty index. The study applied Augmented Dickey-Fuller (ADF) test, correlation analysis, the GARCH (1,1) model, and the Granger Causality test to analyse the interrelationship. The results of correlation matrix show that there is no interrelationship between the two variables. The GARCH (1,1) model found that the NSE Nifty index is not affected by the rainfall index and Granger Causality test displays that rainfall index does not Granger Cause the Nifty index. According to the authors’ knowledge, this is the first empirical study to determine the interrelationship between the rainfall index and the Nifty Index over a longer period of time.